Student Creativity Innovation in Completing Artificial Intelligence (AI)-Based Lecture Assignments - Nadia Aliyatuz Zulfa; Na'imah Na'imah; Nurlaili Dina Hafni; Hibana Hibana; Dwi Aminatus Sa'adah; Malikatus Sholihah; Nurita Sari (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
This study aims to describe the forms of innovation and creativity among students in utilizing Artificial Intelligence (AI) technology to complete academic assignments, as well as to identify the ethical challenges and risks involved. A qualitative phenomenological approach was used, involving eight active students from the Early Childhood Islamic Education (PIAUD) program who frequently use platforms such as ChatGPT, Grammarly, Canva AI, and DALL-E. Data were collected through semi-structured interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. The findings reveal that students use AI not only for technical efficiency but also as a medium to express creativity in essay writing, language editing, and visual media production. However, ethical issues arise, including technological dependency and uncertainty about the authenticity of AI-assisted academic work. This research contributes significantly to the development of AI literacy programs and institutional policies in higher education, promoting responsible AI use while reinforcing students’ independent thinking and learning.